GENDER FACTORS OF SOCIAL AND ECONOMIC DEVELOPMENT OF A COUNTRY - N. Kochkina; A. Stavytskyy (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article discusses the impact of gender asymmetry on the socio-economic development of the country. Authors detected factors that determine with high level of the probability social development of the society. Econometric relationship between the level of GDP per capita in comparative prices and the socio-cultural and gender factors are developed and estimated. The analysis showed that the level of individualism, indulgence, economic participation, and political empowerment of women in the society have direct linear correlation with GDP per capita. Power distance has opposite inverse correlation with the level of GDP. Application of regression analysis gave the possibility to divide all countries into 9 clusters with similar features. Two-dimensional matrix included GDP per capita and coefficient of implementation of a country gender and sociocultural potential. The recommendations for stimulating economic growth by smoothing gender gaps are proposed.